Iranian EFL learners' identity construction in a critical reflective course: a case of an online course. (2nd January 2020) - Rezaei, Saeed; Latifi, Ashkan
ABSTRACT: The present mixed-methods research examined the identity and attitude of Iranian English language learners as a result of their participation in an online critical reflective course. The participants were 38 English language students who attended ten online sessions within a five-month English language course. Their online posts underwent inductive qualitative content analysis and subsequently five themes were extracted. In addition, the content of the first and last two sessions were analysed quantitatively. A validated questionnaire was also administered and 18 participants were interviewed. Qualitative and quantitative content analyses of the data revealed eight finalised codes. The analysis of the findings showed that although the participants' identity and attitudes did not undergo material changes, their awareness of the intercultural and interlingual issues, between Persian and English language and culture, was sharpened. In addition, their online identities proved to be not set off from their offline identities nor identical to them but interrelated.